Introduction to AutoCAD 2011 - Yarwood, A. (Alfred), 1917- (Oxford : Newnes, 2010)
Alf Yarwood's best-selling text provides a comprehensive, step-by-step introduction to the latest release of AutoCAD. It covers all the requirements of City and Guilds courses in Computer Aided Design, Computer Aided Engineering and the drawing modules in BTEC Higher and National Higher Engineering. After beginning with the basic principles and an introduction to 2D technical drawing, he continues with extensive coverage of all 3D topics such as 3D solid modelling and rendering, taking into account all the new features of the 2011 AutoCAD software. The full-colour, clear presentation makes this the best choice for all beginning students of AutoCAD. Accompanied by a comprehensive website with worked solutions, further exercises and multiple choice questions and answers A step-by-step approach using extensive full colour illustrations and screen shots throughout Written by a prominent AutoCAD author who is a member of the Autodesk Developer Network.
Part A. 2D design. Introducing AutoCAD 2011 ; Introducing drawing ; Osnap, AutoSnap and Dynap ; Zoom, Pan and templates ; The Modify tools ; Dimensions and Text ; Orthographic and isometric ; Hatching ; Blocks and Inserts ; Other types of file format ; Sheet Sets -- Part B. 3D design. Introducing 3D modelling ; 3D models in viewports ; The modification of 3D models ; Rendering ; Building drawing ; Three Dimensional Space ; Editing 3D solid models ; Other features of 3D modelling ; Internet tools and Help ; Design and AutoCAD 2011.
Keywords: AutoCAD; Computer-aided design; Electronic books